2006
DOI: 10.1002/clc.4960290205
|View full text |Cite
|
Sign up to set email alerts
|

Acute changes in left ventricular diastolic function: Cigarette smoking versus nicotine gum

Abstract: SummaryBackground: Echocardiographic evidence of diastolic dysfunction has been demonstrated during acute cigarette smoking in patients with coronary artery disease. Similar studies in healthy patients have shown conflicting results. Furthermore, it is unclear whether nicotine or some other cigarette-related substance is responsible for these observations.Hypothesis: The purpose of the study was to confirm or refute acute effects of cigarette smoking on diastolic function in healthy patients and to compare dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 6 publications
0
5
0
1
Order By: Relevance
“…These parameters may explain the differences in diastolic function observed between smokers and electronic cigarette users after smoking and device use. Moreover, a study evaluating the effects of smoking compared to nicotine delivered by gum showed that nicotine alone did not cause acute changes in diastolic function [ 28 ]. It seems that nicotine absorption rate is lower from electronic compared to tobacco cigarette use [ 29 ], even when using new-generation devices [ 30 ]; the difference in haemodynamic response between the two groups may be attributed to this.…”
Section: Discussionmentioning
confidence: 99%
“…These parameters may explain the differences in diastolic function observed between smokers and electronic cigarette users after smoking and device use. Moreover, a study evaluating the effects of smoking compared to nicotine delivered by gum showed that nicotine alone did not cause acute changes in diastolic function [ 28 ]. It seems that nicotine absorption rate is lower from electronic compared to tobacco cigarette use [ 29 ], even when using new-generation devices [ 30 ]; the difference in haemodynamic response between the two groups may be attributed to this.…”
Section: Discussionmentioning
confidence: 99%
“…Considering that nicotine gum chewing does not yield any acute change in LV diastolic performance in young healthy individuals [ 30 ], it is likely that the acute effect of smoking on LV diastolic function may not be due to nicotine alone. A potential role of smoke-induced acute impairment in coronary blood flow could be hypothesized [ 26 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…The deleterious effect of tobacco seems to be independent of the form of use; increased risk for cardiovascular diseases is reported in nonsmoking use of tobacco [ 88 ]. There is no “safe” level of smoking; single cigarette may stiffen the left ventricle [ 89 ], and as few as 1 to 4 cigarettes a day double the risk of myocardial infarction [ 90 ]. Mechanisms leading to heart failure in smokers include (i) indirect effects, that is by causing or aggravating comorbidities that are related with heart failure, and (ii) direct effects on the myocardium [ 91 , 92 ].…”
Section: Lifestyle Changesmentioning
confidence: 99%